Distinguishability between ancient and modern leaded tin bronzes by the composition of their lead inclusions. Issue 2 (16th December 2019) - Shilstein, S.; Berner, A.; Feldman, Y.; Shalev, S.; Rosenberg, Yu.
ABSTRACT: The composition of lead inclusions in modern and ancient leaded tin bronzes was studied by X-Ray Diffraction (XRD) and Energy Dispersive Spectroscopy (EDS) in Scanning Electron Microscope (SEM). Lattice parameter of lead inclusions in all bronzes was smaller than the lattice parameter of pure lead. This determination indicates that lead inclusions in bronzes are nothing else but Pb–Sn solid solutions. Tin concentration in lead inclusions in modern bronzes was not less than 3 at% in accordance with the Pb–Sn phase diagram, tin concentration in lead inclusions of ancient bronzes was as low as 1 at%. This difference enables a distinction between ancient bronze artefacts and modern products including the most sophisticated fakes. On the other hand, our work demonstrates that the generally accepted Pb–Sn phase diagram corresponds to an incomplete equilibrium state and only after centuries-long aging at ambient temperatures does the Pb–Sn solid solution reach real equilibrium.